If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = -2.3(4x + 5) Reorder the terms: 10 = -2.3(5 + 4x) 10 = (5 * -2.3 + 4x * -2.3) 10 = (-11.5 + -9.2x) Solving 10 = -11.5 + -9.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9.2x' to each side of the equation. 10 + 9.2x = -11.5 + -9.2x + 9.2x Combine like terms: -9.2x + 9.2x = 0.0 10 + 9.2x = -11.5 + 0.0 10 + 9.2x = -11.5 Add '-10' to each side of the equation. 10 + -10 + 9.2x = -11.5 + -10 Combine like terms: 10 + -10 = 0 0 + 9.2x = -11.5 + -10 9.2x = -11.5 + -10 Combine like terms: -11.5 + -10 = -21.5 9.2x = -21.5 Divide each side by '9.2'. x = -2.336956522 Simplifying x = -2.336956522
| 18b-21=15b+3 | | 7x-[-5]=-9 | | 4=2.3x+9-1.3x | | 6m=2m-8 | | 2x(28)=x+4 | | 26x+24=-39x-6 | | -6x-9x+11= | | 3.4(x+2)=-1 | | 2x-28=x+4 | | 3n-4=10 | | (6x-9y-4)-(7x-12y-6)= | | 2(4x+-3)+-8=4+2x | | 7.4gr*1200fps= | | 4x^2+21y^2=13 | | 8m=96-16 | | 9-5x=12-(3x-5) | | 6w+6=37 | | 12p=6-3 | | 4*2x-5=6 | | 11x-5=7x+7 | | x/8+6= | | 9=1+m/3 | | (x^2+15)(x^2+3)=0 | | 4(x-3)=-2x+18 | | x+7-15= | | -6*3x+15=18 | | 2b-3=7 | | -6*3x+5=18 | | 11x-3x=12-30 | | x^2(x+15)(x+3)=0 | | 2y^2+5+11y=0 | | y=10+6x |